The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1097/jto.0b013e318168c801
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Disease Control with Erlotinib after Gefitinib Failure in Typical Gefitinib-Sensitive Asian Patients with Non-small Cell Lung Cancer

Abstract: A significant proportion of typical gefitinib-sensitive Asian NSCLC patients can have disease control with erlotinib after gefitinib failure. The role of subsequent administration of a second EGFR TKI after failure of the first TKI in advanced NSCLC should be further pursued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 27 publications
2
48
2
Order By: Relevance
“…Certain clinical characteristics, including response or time to progression (TTP) to previous EGFR-TKI, chemotherapy between EGFR-TKIs, and EGFR-TKI free interval have been examined as predictive markers for the success of EGFR-TKI re-challenge (16)(17)(18)(19)(20)(21). The association between the occurrence of disease control (PR or SD), previous EGFR-TKI and to EGFR-TKI re-challenge has been described frequently, but other markers are controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain clinical characteristics, including response or time to progression (TTP) to previous EGFR-TKI, chemotherapy between EGFR-TKIs, and EGFR-TKI free interval have been examined as predictive markers for the success of EGFR-TKI re-challenge (16)(17)(18)(19)(20)(21). The association between the occurrence of disease control (PR or SD), previous EGFR-TKI and to EGFR-TKI re-challenge has been described frequently, but other markers are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluation of the efficacy of EGFR-TKI re-challenge was limited to patients who achieved good control of disease with the first line of EGFR-TKI, disease control rate and PFS were 56-73% and 3.4-5.6 months, respectively (16)(17)(18)(19)(20)(21). On the other hand, patients whose disease was not be controlled with the first line of EGFR-TKI tended to exhibit poor efficacy with re-challenge (19,20,(22)(23)(24). From these results, the effect of first EGFR-TKI may be considered a predictive marker of efficacy of re-challenge, but specific molecular markers associated with mechanisms of acquired resistance have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Tarceva is the only one that possesses a survival advantage in treating lung cancer (21,22). It is a new targeted therapy drug which can be selected after failed first-or second-line chemotherapy in patients with progressive and metastatic NSCLC (Tarceva received a certification license in the US in 2004 and in the European Union in 2005, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Lynch et al (24) and Paez et al (25) reported that EGFR mutations in lung cancer cells were a prerequisite for targeted drugs. That EGFR mutations are closely related to targeted therapy in NSCLC is widely recognized (13,18,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study of patients with stage IV NSCLC who progressed after previously achieving long term disease control on EGFR TKI treatment, subsequent treatment with standard chemotherapy and, at renewed progression, retreatment with erlotinib (alone or in combination with cetuximab) was considered a viable option [132]. Several evidences support the retreatment with the same [133][134][135][136][137], or different [138][139][140][141][142][143] EGFR-TKI in patients who showed SD during 1st TKI treatment, while lower activity is reported for those patients who had PD to 1st TKI [144]. The highly heterogeneous nature of NSCLC tumours with respect to the mutations causing both the initial tumour and treatment response, which can also change in response to treatment, can create an apparent paradox whereby failure of a treatment at one stage of the disease does not mean that the same treatment might not be beneficial at a later stage.…”
Section: Re-treatment With Egfr Tkis After Having Completed Treatmentmentioning
confidence: 99%